A Profile and Three-Year Follow-Up of Patients with Basal Cell Carcinoma in the Western Cape, South Africa - J. C. Gallo; J. W. Schneider; J. de Wet; K. Moxley; H. F. Jordaan; W. I. Visser; B. Tod (Journal of Skin Cancer)
Background. Basal cell carcinoma (BCC) is an important malignancy in sub-Saharan Africa. There is a paucity of data regarding BCC in South Africa. Aims. To describe the clinicopathological features of patients presenting with BCC in a cohort of South African patients. Methods. This retrospective descriptive study reviewed the medical records of 149 patients with BCC who attended the dermatology clinic at Tygerberg Academic Hospital from September 2015 to August 2016. Demographic and clinical data of those patients with histologically proven BCC were retrieved from clinical records. The data included the assessment for BCC recurrence after three years (September 2016–August 2019). Results. Of 390 patients, 155 (39.7%) had histologically confirmed BCCs. Complete medical records were available for 149 of these patients, and most were male (55.7%) and white (85.9%) with a median age of 70 years. Most patients had their BCC lesions for 12 months (43.1%) before diagnosis. BCCs were mostly located on the head and neck area (58.1%). In most patients (72.0%), a diagnostic punch biopsy confirmed BCC. Plastic surgeons subsequently excised the BCC lesions in 74.0% of these patients. The most common histological subtype was nodular BCC (74.0%). The National Comprehensive Cancer Network (NCCN) risk of recurrence was approximately evenly distributed between high- (54.1%) and low-risk groups (45.9%). The major high-risk feature was the location (36.6%). Histologically confirmed BCC recurrence occurred in 9 of the 149 patients (3.7%) over three years. Conclusions. BCC represents a high burden of disease in our setting. Compared to existing studies, the BCCs in this study are clinically and histologically similar to international reports.